An Application of Multiple Regression Model of Two-Wheeler Industry for Advertising Impact - Gongad, S. S. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Statistical applications are rarely used for conducting research in applied areas. This research is conducting to evaluate an application of multiple regression model for two-wheeler industry and examining the advertising impact on the model. An application of multiple and partial correlation, relative applications on regression model are tested such as collinearity. The results are concluded at the end of the application of model.